2014
DOI: 10.1177/1470320314528364
|View full text |Cite
|
Sign up to set email alerts
|

Aliskiren inhibits prorenin-induced human aortic smooth muscle cell migration

Abstract: Taken together, we provide the first evidence of the inhibitory action of aliskiren on SMC migration induced by prorenin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Myofibroblast migration was detected with a modified Boyden's chamber assay [13]. The cell culture inserts, which contain membranes with 8.0 lm pore size, were placed in a 24-well tissue culture plate (Millipore ECM508, Billerica, MA).…”
Section: Effect Of Vegf-d On Myofibroblast Migrationmentioning
confidence: 99%
“…Myofibroblast migration was detected with a modified Boyden's chamber assay [13]. The cell culture inserts, which contain membranes with 8.0 lm pore size, were placed in a 24-well tissue culture plate (Millipore ECM508, Billerica, MA).…”
Section: Effect Of Vegf-d On Myofibroblast Migrationmentioning
confidence: 99%
“…We attempted to measure active RAC1 and RHOA in migrating ENCDC using sensitive G-LISA kits (Ferri et al, 2014; Nini and Dagnino, 2010), but could not obtain reproducible results. Furthermore, we wanted to measure RAC1 and RHOA activity only in cells that migrated furthest from cultured gut slices (i.e., distal ENCDC, Supplemental Figure 1) because these cells were examined for all other studies.…”
Section: Resultsmentioning
confidence: 99%
“…NP ALIS also significantly decreased collagen content in the aorta. Ferri et al [38] demonstrated the inhibitory action of aliskiren on smooth muscle cell migration induced by prorenin. The inhibitory effect of aliskiren on fibroblast proliferation in AGT-REN double transgenic hypertensive mice in vitro has been documented as well [39].…”
Section: Discussionmentioning
confidence: 99%